The influence of individual entrepreneurial orientation and social relationships on intention to stay amongst engineers: perceived organisational support as a mediating role / Idris Osman - Osman, Idris (2018)
In the process of retaining engineers, organisations are often pressurised to fulfil the various employment expectations outlined by engineers' to lead in innovation, and to remain competitive in uncertainty business demands. Mounting problems of retaining individual engineers are often linked to the limited entrepreneurial paths and social exchange underlying engineers' behavioural intentions. Although the departing behaviour is related to the weakness in this two core aspects, the relationship between individual entrepreneurial orientation and social relationships in predicting engineers' intention to stay is still uncertain.Therefore, this research examined the relationships between individual entrepreneurial orientation (e.g. innovativeness, proactiveness, risk-taking and autonomy), social relationships (e.g. teamwork and trust-in manager) and intention to stay amongst engineers. This research assessed the mediating effect of perceived organisational support on the relationships between individual entrepreneurial orientation, social relationships and intention to stay amongst engineers. Data were collected using a cross-sectional survey, whereby, 572 Malaysian engineers (58.4 percent response rate) from manufacturing companies were recruited as samples. Purposive sampling method was employed to determine the sample size of the study. The research model was analysed using partial least squarestructural equation modelling. Meanwhile, SmartPLS 3.2.6 was used to validate the research model and the proposed hypotheses of the study. The findings from the study confirmed that innovativeness, proactiveness, teamwork, trust-in manager and perceived organisational support positively influenced engineers' intention to stay, but not for risk-taking and autonomy. Findings also showed that intention to stay, proactiveness, risk-taking and trust-in manager significantly and positively correlated to perceived organisational support amongst engineers, but not for innovativeness, autonomy and teamwork. The mediation analysis reported that perceived organisational support had positively mediated the relationships between individual entrepreneurial orientation (innovativeness, proactiveness, risk-taking and autonomy), social relationships (teamwork and trust-in manager) and intention to stay amongst engineers. The research model explained 57.8 percent of the substantial amount of variance in intention to stay model. This research theoretically contributed to the extension of entrepreneurial orientation theory and social exchange theory in predicting engineers' intention to stay. It was confirmed that individual entrepreneurial orientation could be used to predict engineers' intention to stay. Teamwork and trust-in manager also contributed to the engineers' social relationships, thus, increasing their intention to stay within organisations. Practical contributions were explained the implications of research to different levels, such as nation, industry, organisations, individual engineers and policymakers. The limitations of this study were discussed, and recommendations for future research concerning the improvisation of intention to stay model and variables presentation amongst engineers and other types of workers were also suggested.